Tanfīdh Barāmij Maḥjar al-ʿArabī fī Mahārat al-Kalām li-Tilāmidh aṣ-Ṣaff al-Mutafawwiq bi-Maʿhad Dār aṣ-Ṣibyān Balung: Implementation of the Arabic Corner Program in Speaking Skills for Outstanding Students at Dār aṣ-Ṣibyān Balung - Hamami Abicandra, Muh. Nidom; Ardytama, Genta (Critical Review of English-Arabic World Journal, 2025)
نعلم خلافا تعلم اللغة العربية تعد مهارة الكلام وإحدى المهارات الأساسية التي يجب على كل طلاب إتقانها وهي أهداف الأساسية والنهائية لتعلم اللغة أجنبية، فإن أنشطة تحدث في فصل المتفوق له جانب إتصال ثنائى الإتجاه أى أنشطة بين متحدث ومستمع بطريقة متبادلة أو يسمى بمحادثة، وبا لتالي يجب أن تعتمد علي ممارسة أولا على قدرة التلاميذ على تعليم مهارة الكلام  في اللغة العربية و صنع رئيس المعهد بمحجر العربية لإهتمام التعليم اللغة العربية وحفظ بيئة اللغوية  لطلاب فصل المتفوقة بمعهد دار الصبيان كارنج دورين بالونج وأهداف الذي رسمنا منذ البداية من هذه البحوثة علي وهي نعرف كيفية عملية تنفيذ برامج مهجر العربي بمعهد دار الصبيان وكذلك نعرف كيفية عملية دافعة والعائقة بتنفيذ محجر العربية لطلاب فصل المتفوقة. استخدم هذا البحث مدخلا كيفي من خلال طريقة الوصفية و مصادر البيانات استخدم الباحث بمصادر الإنسانية وغير الإنسانية أى بملاحظة ومقابلة ووثائق. وحصول علي هذا البحث إستنادا علي أهداف بحثه هو عملية تنفيذ محجر العربي يعمل بثلاثين أيام و فيه كثير من أنواع البرامج التي يؤثر على ترقية مهارة الكلام وهناك عوامل الدافعة أكثر من عوامل العائقة بهذا البرنامج وبسبب محجر العربي بيئة اللغوية وشجاعة الطلاب صار أجود بنصبة قبله. Teaching Arabic language differs from other subjects because speaking is one of the essential skills that every student must master; it is a fundamental and ultimate goal of learning a foreign language. Speaking activities in the advanced class involve two-way communication, meaning activities between a speaker and a listener in an interactive manner, also called conversation. Therefore, it should primarily rely on practicing students’ ability to develop speaking skills in Arabic. The head of the institute established the Arabic Immersion Program to promote Arabic language education and preserve the linguistic environment for students in the advanced class at Dar Al-Subyan School, Kareng Durin, Balung. The objectives of this study are to understand how the Arabic Immersion Program is implemented at Dar Al-Subyan School and to identify the driving and inhibiting factors affecting its implementation for the advanced students. This research uses a qualitative approach with a descriptive method. The data sources include human and non-human sources, obtained through observation, interviews, and documentation. Based on the research findings, the Arabic Immersion Program is implemented over a period of thirty days and includes various types of activities that positively influence the improvement of speaking skills. The program has more driving factors than inhibiting factors. Thanks to the Arabic Immersion Program, the linguistic environment and students’ courage have significantly improved compared to before its implementation.